2019
DOI: 10.1542/peds.2017-3536
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Retail Licensing and Youth Product Use

Abstract: BACKGROUND: Restricting youth access to tobacco is a central feature of US tobacco regulatory policy, but impact of local tobacco retail licensing (TRL) regulation on cigarette smoking rates remains uncertain. Effects of TRL on other tobacco product use and use as adolescents reach the age to legally purchase tobacco products has not been investigated. METHODS: Prevalences of ever and past 30-day cigarette, electronic cigarette (e-cigarette), cigar, and hookah use were assessed in a survey of a cohort of 1553 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…We also observed an association of retail license requirements with a lower rate of e-cigarette use in adults. The retail license requirement as a strategy to regulate e-cigarettes has aroused public attention, because a recent study 42 found that youth who live in areas with strong tobacco vendor licensing requirements have lower rates of tobacco use and e-cigarette use. However, federal law does not require retailers to have a license to sell e-cigarettes, 31 and fewer than one-third of states require e-cigarette retailers to be licensed.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed an association of retail license requirements with a lower rate of e-cigarette use in adults. The retail license requirement as a strategy to regulate e-cigarettes has aroused public attention, because a recent study 42 found that youth who live in areas with strong tobacco vendor licensing requirements have lower rates of tobacco use and e-cigarette use. However, federal law does not require retailers to have a license to sell e-cigarettes, 31 and fewer than one-third of states require e-cigarette retailers to be licensed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to past findings showing that retail access laws are associated with a reduction in tobacco sales and retailer density [12e15], e-cigarette retail licensing may be a useful policy tool to reduce e-cigarette use among adolescents. In a prior study, Astor et al [16] found that 11th and 12th grade adolescents living in jurisdictions with the most restrictive ordinances on tobacco products had lower odds of cigarette use compared with those living in areas with less strict tobacco retail licensing regulations. Another study hypothesized that tobacco retailer licensing policies might allow for more effective enforcement because such laws require a current list of tobacco vendors [17].…”
Section: Discussionmentioning
confidence: 97%
“…Prior research has demonstrated that requiring businesses to obtain a TRL reduces the number of businesses that sell tobacco products 47 and reduces daily smoking rates by 2% for each 1% increase in retailer compliance. 19…”
Section: Discussionmentioning
confidence: 99%